Use of STEAM Approaches in K-12 Education: A Review - Basnet, Amin Kumar (Journal of Multidisciplinary Research Advancements, 2026)
STEAM education is growing in prominence as a competency-based framework that provides K-12 students with essential 21st-century skills. Although the article has a theoretical basis, there are notable loopholes in understanding its practical implementation and in evaluating intricate skills development. This review summarises contemporary evidence on the application of STEAM in K-12 education, based on 16 peer-reviewed works published between 2018 and 2025 in ERIC. This investigates two main research questions: (i) how the theoretical foundation of STEAM is translated into practical pedagogy, and (ii) the status of challenges related to assessment and skill development. The findings suggest that the theoretical basis of STEAM is predominantly enacted through integrated, inquiry-based approaches, especially through Project-Based Learning (PBL) and Design Thinking (DT), alongside Arts integration for creative visualisation and iterative problem-solving. These pedagogies help the students to develop creativity, collaboration, and metacognition. The review outlines several challenges to the sustainable adoption of interdisciplinary practices. It includes the inequitable distribution of teachers trained in interdisciplinary practices and the lack of appropriate tools to assess process-oriented skills. There is a need to invest in teacher development and to adapt assessment strategies to align with new STEAM teaching approaches.